"Step Out of the Cycle": Needs, challenges, and successes of international undergraduates at a U.S. University. (April 2017) - Caplan, Nigel A.; Stevens, Scott G.
Abstract: A triangulated, mixed-methods needs analysis was conducted in order to inform the redesign of the English for Academic Purposes program that provides conditional undergraduate admission to a mid-sized U.S. university. Online surveys were completed by 191 students and 226 faculty. Although they largely agreed on the importance of 21 tasks and activities in undergraduate classes, students rated themselves as significantly more successful on most of them than did faculty. Qualitative data from open-ended comments and interviews with five international students provided both insight and complexity to the quantitative data. Factors for success (including persistence and engagement) and challenges for international students (linguistic, cultural, and academic) were identified as well as a need for greater tolerance from faculty and domestic students and better awareness and use of support services. Pedagogically, while academic literacy remains vital to university success, oral communication skills, especially the ability to engage in discussions and group work, are equally if not more important for international students. Highlights: A triangulated, mixed-methods needs analysis was conducted for undergraduate students. 21 tasks and activities were similarly ranked in importance by students and faculty. Oral communication and cultural schema are at least as important as writing skills. Persistence and engagement were factors for success among international students. Linguistic, cultural, and academic challenges overlap.